White noise enhances new-word learning in healthy adults. Issue 1 (December 2017) - Angwin, Anthony; Wilson, Wayne; Arnott, Wendy; Signorini, Annabelle; Barry, Robert; Copland, David
Abstract Research suggests that listening to white noise may improve some aspects of cognitive performance in individuals with lower attention. This study investigated the impact of white noise on new word learning in healthy young adults, and whether this effect was mediated by executive attention skills. Eighty participants completed a single training session to learn the names of twenty novel objects. The session comprised 5 learning phases, each followed by a recall test. A final recognition test was also administered. Half the participants listened to white noise during the learning phases, and half completed the learning in silence. The noise group demonstrated superior recall accuracy over time, which was not impacted by participant attentional capacity. Recognition accuracy was near ceiling for both groups. These findings suggest that white noise has the capacity to enhance lexical acquisition.